2016
DOI: 10.1142/s0219633616500541
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation and free energy analysis of the interaction of platinum-based anti-cancer drugs with DNA

Abstract: Cisplatin and oxaliplatin are two widely-used anti-cancer drugs which covalently bind to a same location in DNA strands. Platinum agents make intrastrand and interstrand cross-links with the N7 atoms of guanine nucleotides which prevent DNA from polymerization by causing a distortion in the double helix. Molecular dynamics simulations and free energy calculations were carried out to investigate the binding of two platinum-based anti-cancer drugs with DNA. We compared the binding of these drugs which differ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Moreover, Zn(en)Cl 2 fairly bound to the binding site of the DNA during the simulation. The higher RMSD value of the complex, the more unstable the drug-DNA structural quality upon ligand binding, so the RMSD with the lowest value is preferred due to the minimal structural change during the simulation (Jalili et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zn(en)Cl 2 fairly bound to the binding site of the DNA during the simulation. The higher RMSD value of the complex, the more unstable the drug-DNA structural quality upon ligand binding, so the RMSD with the lowest value is preferred due to the minimal structural change during the simulation (Jalili et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There were also several studies involving small ligands binding to nucleic acids. Interactions of anticancer compounds with DNA, such as cisplatin and oxaliplatin (Jalili et al, 2016 ), distamycin with the DNA minor groove (Jalili and Maddah, 2017 ), and plant alkaloid chelerythrine with the human telomere sequence (Ghosh et al, 2015 ) were reported. Aminobenzimidazole binding to an internal ribosome entry site was studied for its anti-hepatitis C virus effect (Henriksen et al, 2014 ).…”
Section: Applications Of Mmpbsamentioning
confidence: 99%